Advancing Paradox Resolution Theory for Interpreting non-profit, Commercial, Entrepreneurial Strategies - Lloyd, S.; Woodside, Arch (Taylor and Francis, 2015)
This study examines the commercial strategies of two non-profit organizations (NPOs) and the alignment of their values and identity while pursuing commercial entrepreneurial strategies. The research uses qualitative, semi-structured, one-on-one interviews conducted in the context of the informants' daily lives and work. The research indicates the value of the alignment of organizational identity with commercial activities as a means for paradox resolution. Lérins and St John are cases of NPOs that engage in strategic choice. Research has yet to examine the role of organizational identity alignment in examining paradox resolution among NPOs. The NPOs engage in strategic choice for which continuous reference to enactment with core values is an important influence on strategic brand-community building behaviour.